2013
DOI: 10.1186/1476-7120-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking echocardiography-determined measures of global and regional left ventricular function correlate with functional capacity in patients with and without preserved ejection fraction

Abstract: BackgroundStandard measures of left ventricular systolic and diastolic function often fail to identify left ventricular dysfunction in patients with heart failure and do not correlate with measures of functional capacity.AimTo determine if speckle tracking echocardiography (STE)–determined measures of global and regional myocardial contractility have a linear association with functional capacity in patients with and without preserved ejection fraction.MethodsIn 68 adult patients, functional status was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…However, in our clinical center, the CPET is widely used in the clinical assessment of patients with HF and the main objective of this study was to explore the relationship between the exercise capacity parameters (VO 2, VE/VCO 2 ) and 3D-STE imaging of LV function in the HF patients with reduced LVEF. We observed a significantly positive correlation between the peak VO 2 values and parameters of 3DE, and a significantly negative correlation between the VE/VCO 2 slope values and the parameters of 3DE which is in agreement with the previously reported results 34,35 . Namely, Peterson et al 34 stated that the 3D-STE measures had a strong linear association with estimates of functional capacity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in our clinical center, the CPET is widely used in the clinical assessment of patients with HF and the main objective of this study was to explore the relationship between the exercise capacity parameters (VO 2, VE/VCO 2 ) and 3D-STE imaging of LV function in the HF patients with reduced LVEF. We observed a significantly positive correlation between the peak VO 2 values and parameters of 3DE, and a significantly negative correlation between the VE/VCO 2 slope values and the parameters of 3DE which is in agreement with the previously reported results 34,35 . Namely, Peterson et al 34 stated that the 3D-STE measures had a strong linear association with estimates of functional capacity.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a significantly positive correlation between the peak VO 2 values and parameters of 3DE, and a significantly negative correlation between the VE/VCO 2 slope values and the parameters of 3DE which is in agreement with the previously reported results 34,35 . Namely, Peterson et al 34 stated that the 3D-STE measures had a strong linear association with estimates of functional capacity. Additionally, Donal et al 35 reported a moderate correlation between 3D-STE and the functional capacity parameters.…”
Section: Discussionsupporting
confidence: 93%
“…However, the potential accuracy of the method in computing the myocardium wall strains has yet to be confirmed by a first patient study [12]. Three-dimensional speckle tracking echocardiography is also widely adopted for measuring the circumferential, radial and longitudinal strains in the myocardium [13,14]. Kleijn et al [15] determined the regional function of the myocardium based on automatic wall motion analysis using three-dimensional speckle tracking echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…Despite current therapeutic approaches, HFpEF related mortality remains high, and no specific treatment has proved effective . In those patients, studies identified different echocardiographic predictors of clinical outcome, quality of life and functional capacity . Also in them, limited exercise capacity and deteriorating quality of life correlated with poor prognosis similar to patients with heart failure with reduced ejection fraction (HFrEF) .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In those patients, studies identified different echocardiographic predictors of clinical outcome, [5][6][7] quality of life 8,9 and functional capacity. 10,11 Also in them, limited exercise capacity and deteriorating quality of life correlated with poor prognosis similar to patients with heart failure with reduced ejection fraction (HFrEF). 12,13 Although the most accurate surrogate of functional capacity is peak oxygen uptake (peak VO 2 ), 14 its assessment is limited in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%